Method for preparing subgrade water stable layer from solid waste phosphogypsum, aluminum ash and steel slag

CN118026627BActive Publication Date: 2026-10-27BEIJING MINING & METALLURGICAL TECH GRP CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202410035522.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-10
Publication Date
2026-10-27
Estimated Expiration
2044-01-10

AI Technical Summary

Technical Problem

磷石膏利用率不足39%,杂质可溶P2O5与可溶F的浸出能造成地表污染

Benefits of technology

[0019]1、本发明是方法使得磷石膏中的可溶HPO42-、H2PO4-、F-以及铝灰中Al、AlN、NaCl、KF都能得到有效去除或分离,消除环境污染风险和水化负作用,可大规模减少水泥和天然碎石的使用;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118026627B_ABST
    Figure CN118026627B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing a roadbed water stable layer from solid waste phosphogypsum, aluminum ash and steel slag, wherein fine powder and cement are mixed to form a solid waste-based composite cementitious material by modifying the phosphogypsum through vacuum heating, modifying the aluminum ash through high-temperature calcination and modifying the steel slag through grinding, and then the solid waste-based composite cementitious material is mixed with special steel slag-gravel particle size range and proportion to form a mixed aggregate to prepare the roadbed water stable layer. The application has the following advantages: soluble HPO4 2‑ , H2PO4 ‑ , F ‑ in the phosphogypsum and Al, AlN, NaCl and KF in the aluminum ash can be effectively removed or separated, the environmental pollution risk and hydration negative effect are eliminated, and the use of cement and natural gravel can be greatly reduced; the steel slag, the aluminum ash and the phosphogypsum are synergistically and resourcefully utilized in the roadbed water stable layer, the utilization rate of the solid waste is high; the compressive strength without limit is higher than that of the Portland cement stabilized steel slag-gravel inter-mixed aggregate; and the strength of the water stable layer is enhanced by generating more fibrous morphology calcium aluminate hydrate (C-A-H) crystals and long columnar ettringite (AFt).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a roadbed water-stabilized layer from solid waste phosphogypsum, aluminum ash, and steel slag, belonging to the field of roadbed material technology. Background Technology

[0002] Aluminum ash (AD), phosphogypsum (PG), and steel slag (SS) are industrial solid wastes generated during aluminum electrolysis, wet-process phosphoric acid production, and steelmaking, respectively. Aluminum ash is classified as hazardous solid waste, yet its utilization rate is less than 10%, and its pollutants include Al, AlN, AlF3, chlorides, fluorides, and toxic gases. Phosphogypsum has a utilization rate of less than 39%, and the leaching of impurities such as soluble P2O5 and soluble F can cause surface pollution. It is evident that innovative and large-scale technologies for the efficient utilization and resource recovery of solid waste have broad application prospects.

[0003] In the latest aluminum ash resource utilization technologies, patent CN202222303022.8 uses crushing + multi-layer filtration technology to classify aluminum ash slag before further processing. Patent CN202310982349.9 mixes aluminum ash, phosphoric acid, and recalcined magnesium oxide for calcination to prepare refractory materials. Patent CN202210750673.3 grinds, grades, and filters aluminum ash before wet mixing and heat treatment with calcium hydroxide and sodium hydroxide solutions to obtain concrete materials. It can be seen that the existing aluminum ash recycling technologies face challenges in four aspects: complex processes, incomplete recycling, numerous byproducts, and high processing costs.

[0004] In the latest phosphogypsum resource utilization technologies, patent CN202310593051.9 describes the preparation of cement retarder by double-slurrying phosphogypsum and adding modifiers; patent CN202211065081.4 describes the preparation of impermeable materials by mixing phosphogypsum, PMSB5, and polymer flocculants; and patent CN202210728725.7 discloses a method for preparing building gypsum by recrystallizing phosphogypsum and then air-drying to remove free water. It is clear that existing phosphogypsum building material utilization technologies still suffer from drawbacks such as complex processing procedures and high levels of secondary pollution.

[0005] Among the latest steel slag resource utilization technologies, patent CN202010196416.0 describes soaking steel slag in an aqueous solution of iron-oxidizing bacteria, followed by drying and grinding to prepare steel slag powder. Patent CN202311127652.7 uses steel slag as the main raw material, subjecting it to sulfidation and carbonization treatments for the production of steel slag-based cementitious materials and aggregates. Patent CN201911059106.8 enhances the chemical activity of steel slag by connecting multi-stage crushing equipment, drying equipment, conveyors, and reactors. Overall, these technologies have not completely solved or overcome the shortcomings of low activity and easy expansion of steel slag, and the processes are becoming increasingly complex, which is not conducive to the large-scale utilization of steel slag.

[0006] Analysis of existing technologies reveals a current lack of resource utilization technologies that minimize secondary pollution, simplify processes, and enable the synergistic utilization of multiple solid wastes. Summary of the Invention

[0007] The technical problem to be solved by this invention is to provide a method for preparing a roadbed water-stabilized layer from solid waste phosphogypsum, aluminum ash, and steel slag, thereby realizing the coupled utilization of multiple industrial solid wastes. That is, it makes full use of the complementary chemical composition between steel slag, aluminum ash, and phosphogypsum, and uses them for simple pretreatment to prepare high-performance roadbed water-stabilized materials. This method can meet the needs of large-scale utilization of solid waste and can significantly reduce the use of cement and natural crushed stone. This invention can achieve the harmlessness of solid waste, produce high-strength roadbed water-stabilized materials, and effectively reduce highway construction costs.

[0008] This invention is achieved through the following scheme: a method for preparing a roadbed water-stabilized layer using solid waste phosphogypsum, aluminum ash, and steel slag, which is prepared from solid waste-based cementitious materials and aggregates. The solid waste-based cementitious materials consist of: heat-treated phosphogypsum, heat-treated aluminum ash, steel slag powder, and 42.5 silicate cement. The aggregates consist of a mixture of hot-quenched steel slag and crushed stone.

[0009] The method for stabilizing steel slag-crushed stone with solid waste-based cementitious material is as follows: the water content is controlled at 7.5%-8.5%; the aggregate soaking time is 12-16 hours; the curing conditions are 23℃-27℃ and humidity is 94.5%-95.5%.

[0010] The content of each component of the solid waste-based cementitious material is as follows: by mass percentage, 16%-24% heat-treated phosphogypsum, 8%-12% heat-treated aluminum ash, 16%-24% steel slag powder, and 40%-60% 42.5 silicate cement.

[0011] The heat treatment method of the phosphogypsum is as follows: lime is added to the phosphogypsum, mixed evenly, heated under vacuum conditions, and finally thermally crushed.

[0012] The amount of lime added is 1-2% of the weight of the phosphogypsum, the mixing time is 2-3 minutes, the atmospheric pressure is controlled at 0.08-0.11 MPa, the heating temperature is controlled between 150℃ and 170℃, the heating time is 60-120 minutes, the thermal crushing time of the phosphogypsum is 2-3 minutes, and the particle size of the thermally crushed phosphogypsum is less than 0.30 mm.

[0013] The heat treatment method for the aluminum ash is as follows: increase the temperature gradient by 8-12℃ / min, raise the temperature to 750-800℃, hold for 30 minutes, raise the temperature to 850-950℃, hold for 60-120 minutes, and then cool down to 150-200℃ before hot crushing.

[0014] The thermal crushing time of the aluminum ash is 4-6 minutes, and the particle size of the thermally crushed aluminum ash is less than 0.30 mm.

[0015] The preparation method of the steel slag powder is as follows: hot-quenched steel slag particles with a particle size in the range of 0.3mm-0.8mm are used, ground with a three-head grinder, and sieved to make the particle size less than 0.10mm.

[0016] The aggregate composition is as follows: a mixture of steel slag and crushed stone with a particle size range of 26.5mm-20.0mm, a mixture of steel slag and crushed stone with a particle size range of 20.0mm-15.0mm, a mixture of steel slag and crushed stone with a particle size range of 15.0mm-10.0mm, a mixture of steel slag and crushed stone with a particle size range of 10.0mm-4.75mm, steel slag with a particle size range of 4.75mm-2.36mm, steel slag with a particle size range of 2.36mm-0.8mm, steel slag with a particle size range of 0.8mm-0.3mm, and steel slag with a particle size range of 0.10mm-0.3mm.

[0017] By mass percentage, the proportions of steel slag and crushed stone with particle sizes ranging from 26.5mm to 20.0mm are both 2.5% to 3.5%; the proportions of steel slag and crushed stone with particle sizes ranging from 20.0mm to 15.0mm are both 7.0% to 8.0%; the proportions of steel slag and crushed stone with particle sizes ranging from 15.0mm to 10.0mm are both 5.5% to 6.5%; and the proportions of steel slag and crushed stone with particle sizes ranging from 10.0mm to 4.75mm are both [missing percentage]. The proportion of steel slag with a particle size of 4.75mm-2.36mm is 16.5%-17.5%, the proportion of steel slag with a particle size of 2.36mm-0.8mm is 16.5%-17.5%, the proportion of steel slag with a particle size of 0.8mm-0.3mm is 4.5%-5.5%, and the proportion of steel slag with a particle size of 0.10mm-0.3mm is 9.5%-10.5%.

[0018] The beneficial effects of this invention are as follows:

[0019] 1. This invention provides a method for removing soluble HPO4 from phosphogypsum. 2- H2PO4 - F - Furthermore, Al, AlN, NaCl, and KF in aluminum ash can be effectively removed or separated, eliminating environmental pollution risks and negative effects of hydration, and significantly reducing the use of cement and natural crushed stone.

[0020] 2. This invention realizes the synergistic resource utilization of steel slag, aluminum ash, and phosphogypsum in the water-stabilized layer of roadbed, with a high solid waste utilization rate;

[0021] 3. In the heat treatment process, the phosphogypsum of the present invention achieves the fixation of soluble phosphorus and soluble phosphorus, eliminates the risk of excessive leaching of soluble phosphorus and soluble phosphorus, and utilizes a vacuum environment to accelerate the conversion rate of dihydrate gypsum to hemihydrate gypsum and improve the hydration strength.

[0022] 4. The aluminum ash of the present invention eliminates the drawbacks of AlN ammonia release and specimen expansion and damage during heat treatment, removes F and Cl corrosion on hydrated specimens by thermal sublimation, and at the same time ensures the hydration activity of Al2O3, promoting the formation of more hydration gel calcium aluminate hydrate and ettringite.

[0023] 5. The steel slag powder used in this invention has a reasonable particle size and possesses both hydration and cementation bonding capabilities as well as the ability to fill micropores and increase density.

[0024] 6. The present invention, through the rational blending of modified phosphogypsum, modified aluminum ash, port miscellaneous micro powder, and silicate cement, produces a novel roadbed water-stabilized cementitious material whose strength can be improved through gypsum hardening, calcium aluminate hydrate formation, and ettringite formation.

[0025] 7. The present invention has a reasonable gradation. By continuously exploring the particle size ratio of steel slag to crushed stone, the utilization rate of steel slag is improved, and the micro-expansion characteristics of steel slag are utilized to reduce the risk of drying shrinkage and cracking of common silicate cement stabilized crushed stone.

[0026] 8. This invention uses a novel roadbed water-stabilized cementitious material to stabilize steel slag-crushed stone aggregate, which has an undetermined compressive strength higher than that of steel slag-crushed stone aggregate stabilized by all silicate cement.

[0027] 9. This invention optimizes the aggregate structure of the water-stabilized layer by compounding medium-sized steel slag with natural crushed stone and replacing crushed stone with fine-sized steel slag.

[0028] 10. The present invention can enhance the strength of the water-stabilized layer by generating more fibrous calcium aluminate (CAH) crystals and long columnar ettringite (AFt);

[0029] 11. The steel slag addition rate in the aggregate of the present invention can be as high as 73.5%, and the aluminum ash addition rate in the solid waste-based cementitious material can be as high as 10%, the phosphogypsum addition rate can be as high as 20%, and the steel slag addition rate can be as high as 20%, resulting in a high overall solid waste utilization rate. Attached Figure Description

[0030] Figure 1 This is a microstructure diagram of the hardened slurry of specimen E2 of the present invention.

[0031] Figure 2 This is a microstructure diagram of the hardened slurry of specimen A of the present invention. Detailed Implementation

[0032] The following is combined Figure 1-2The present invention will be further described, but the scope of protection of the present invention is not limited to the contents described herein.

[0033] For clarity, not all features of the actual embodiments will be described. In the following description, well-known functions and structures will not be described in detail, as they would confuse the invention with unnecessary details. It should be understood that in the development of any actual embodiment, a great deal of implementation detail must be made to achieve the developer’s specific goals, such as changing one embodiment to another according to the limitations of the system or business. In addition, it should be understood that such development work may be complex and time-consuming, but is merely routine work for those skilled in the art.

[0034] A method for preparing a roadbed water-stabilized layer using solid waste phosphogypsum, aluminum ash, and steel slag, comprising solid waste-based cementitious materials and aggregates, wherein the solid waste-based cementitious materials consist of heat-treated phosphogypsum, heat-treated aluminum ash, steel slag powder, and 42.5 silicate cement, and the aggregates consist of a mixture of hot-quenched steel slag and crushed stone.

[0035] The method for stabilizing steel slag-crushed stone with solid waste-based cementitious materials is as follows: the water content is controlled at 7.5%-8.5%; the aggregate soaking time is 12-16 hours; the curing conditions are 23℃-27℃ and humidity is 94.5%-95.5%.

[0036] The content of each component in the solid waste-based cementitious material is as follows (by mass percentage): 16%-24% heat-treated phosphogypsum, 8%-12% heat-treated aluminum ash, 16%-24% steel slag powder, and 40%-60% 42.5 silicate cement.

[0037] The heat treatment method for phosphogypsum is as follows: lime is added to phosphogypsum, mixed evenly, heated under vacuum conditions, and finally thermally crushed.

[0038] The amount of lime added is 1-2% of the weight of the phosphogypsum, the mixing time is 2-3 minutes, the atmospheric pressure is controlled at 0.08-0.11 MPa, the heating temperature is controlled between 150℃ and 170℃, the heating time is 60-120 minutes, the thermal crushing time of the phosphogypsum is 2-3 minutes, and the particle size of the thermally crushed phosphogypsum is less than 0.30 mm.

[0039] The heat treatment method for aluminum ash is as follows: the temperature gradient is increased by 8-12℃ / min, the temperature is increased to 750-800℃, and the temperature is held for 30 minutes. Then the temperature is increased to 850-950℃ and held for 60-120 minutes. After cooling to 150-200℃, the aluminum ash is thermally crushed. The thermal crushing time is 4-6 minutes. The particle size of the aluminum ash after thermal crushing is less than 0.30mm.

[0040] The preparation method of steel slag powder is as follows: hot-quenched steel slag particles with a particle size in the range of 0.3mm-0.8mm are used, ground with a three-head grinder, and sieved to make the particle size less than 0.10mm.

[0041] The aggregate composition is as follows (by mass percentage): 2.5%-3.5% for steel slag and crushed stone with a particle size range of 26.5mm-20.0mm, 7.0%-8.0% for steel slag and crushed stone with a particle size range of 20.0mm-15.0mm, 5.5%-6.5% for steel slag and crushed stone with a particle size range of 15.0mm-10.0mm, and [the remaining percentage is missing from the original text]. The proportions of steel slag are all 8.5%-11.5%, with steel slag in the particle size range of 4.75mm-2.36mm accounting for 16.5%-17.5%, steel slag in the particle size range of 2.36mm-0.8mm accounting for 16.5%-17.5%, steel slag in the particle size range of 0.8mm-0.3mm accounting for 4.5%-5.5%, and steel slag in the particle size range of 0.10mm-0.3mm accounting for 9.5%-10.5%.

[0042] Example 1: The effect of steel slag-crushed stone gradation formula 1 on the strength of water-stabilized layer, and its implementation steps are as follows:

[0043] Step 1: Take the hot slag and crush it using a jaw crusher. Separate the slag particles with diameters in the following ranges: 26.5mm-20.0mm, 20.0mm-15.0mm, 15.0mm-10.0mm, 10.0mm-4.75mm, 4.75mm-2.36mm, 2.36mm-0.8mm, 0.8mm-0.3mm, and 0.1mm-0.3mm.

[0044] Step 2: Weigh steel slag and natural crushed stone within different particle size ranges from Step 1 according to the E1 mixed aggregate formula in Table 1 to form mixed aggregate;

[0045] Step 3: Stabilize the E1 aggregate mixture using all cement as the water-stabilized binder. The process refers to the sampling, preparation, and curing procedures in the "Test Procedures for Inorganic Binder Stabilized Materials in Highway Engineering" JTG E51-2009.

[0046] Step 4: Test the unconfined compressive strength (UCS) and splitting tensile strength (SCS) of E1 specimens after 7, 14, and 28 days of curing. The procedure follows the strength analysis procedure in JTG E51-2009, "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering". The strength test results are shown in Table 1.

[0047]

[0048] Example 2: The effect of steel slag-crushed stone gradation formula 2 on the strength of the water-stabilized layer. Except for the use of E2 as the mixed formula, the other implementation steps are the same as in Example 1. The strength test results are shown in Table 1.

[0049] Example 3: The effect of steel slag-crushed stone gradation formula 3 on the strength of the water-stabilized layer. Except for the use of E3 as the mixed formula, the other implementation steps are the same as in Example 1. The strength test results are shown in Table 1.

[0050] Example 4: Analysis of the effect of heat-treated aluminum ash-heat-treated phosphogypsum-finely ground steel slag powder-silicate cement stabilized steel slag-crushed stone gradation formula 2 on strength. The implementation steps are as follows:

[0051] Step 1: Take the hot slag and crush it using a jaw crusher. Separate the slag particles with diameters in the following ranges: 26.5mm-20.0mm, 20.0mm-15.0mm, 15.0mm-10.0mm, 10.0mm-4.75mm, 4.75mm-2.36mm, 2.36mm-0.8mm, 0.8mm-0.3mm, and 0.1mm-0.3mm.

[0052] Step 2: Weigh steel slag and natural crushed stone of different particle size ranges from Step 1 according to the E2 mixed aggregate formula in Table 1 to form mixed aggregate;

[0053] Step 3: Add 1% lime to the phosphogypsum, mix well for 2 minutes, heat at 150℃ under atmospheric pressure of 0.08MPa for 60 minutes, and then thermally crush for 2 minutes to reduce the particle size to less than 0.30mm.

[0054] Step 4: In a muffle furnace, the aluminum ash is heated to 750°C at a temperature gradient of 8°C / min, held for 30 minutes, then heated to 850°C and held for 60 minutes. After cooling to 150°C, it is thermally crushed for 4 minutes to reduce the particle size to less than 0.30 mm.

[0055] Step 5: Select hot-quenched steel slag particles with a particle size in the range of 0.3mm-0.8mm, grind them with a three-head grinder, and sieve them to obtain steel slag powder with a particle size of less than 0.10mm;

[0056] Step 6: Mix 20% heat-treated phosphogypsum, 10% heat-treated aluminum ash, 20% steel slag powder, and 50% 42.5 silicate cement evenly to obtain a composite cementitious material of heat-treated aluminum ash, heat-treated phosphogypsum, finely ground steel slag powder, and silicate cement.

[0057] Step 7: Stabilize the E2 aggregate mixture with the heat-treated aluminum ash, heat-treated phosphogypsum, finely ground steel slag powder, and silicate cement composite water-stabilized cementitious material prepared in Step 6. Control the water content at 7.5%; the aggregate soaking time is 12 hours; the curing conditions are 23℃ and 94.5% humidity. Other steps refer to the standard specifications of "Test Procedures for Inorganic Binder Stabilized Materials in Highway Engineering" JTGE51-2009.

[0058] Step 8: Test the unconfined compressive strength (UCS) and splitting tensile strength (SCS) of specimen A after 7, 14, and 28 days of curing, following the strength analysis procedure in the "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering" JTG E51-2009. The test results are shown in Table 1.

[0059] Step Nine: The nitrogen (N) content of the hardened specimen A (cured for 28 days), untreated phosphogypsum, and untreated aluminum ash was analyzed by energy dispersive spectroscopy (EDS). Then, leaching was performed according to the "Solid Waste Leaching Toxicity Leaching Method - Horizontal Oscillation Method" (HJ 557-2010). Finally, the soluble phosphorus (P) leaching concentration was determined by ultraviolet-visible spectrophotometry, and the soluble phosphorus (F) leaching concentration was tested using the fluoride ion selective electrode method. The test results are shown in Table 2.

[0060] Example 5: Analysis of the effect of heat-treated aluminum ash-heat-treated phosphogypsum-finely ground steel slag powder-silicate cement stabilized steel slag-crushed stone gradation formula 2 on strength. The implementation steps are as follows:

[0061] Step 1: Take the hot slag and crush it using a jaw crusher. Separate the slag particles with diameters in the following ranges: 26.5mm-20.0mm, 20.0mm-15.0mm, 15.0mm-10.0mm, 10.0mm-4.75mm, 4.75mm-2.36mm, 2.36mm-0.8mm, 0.8mm-0.3mm, and 0.1mm-0.3mm.

[0062] Step 2: Weigh steel slag and natural crushed stone of different particle size ranges from Step 1 according to the E2 mixed aggregate formula in Table 1 to form mixed aggregate;

[0063] Step 3: Add 2% lime to the phosphogypsum, mix well for 3 minutes, heat at 170℃ under atmospheric pressure of 0.11 MPa for 120 minutes, and then thermally crush for 3 minutes to reduce the particle size to less than 0.30 mm.

[0064] Step 4: The aluminum ash is heated to 800℃ in a muffle furnace at a temperature gradient of 12℃ / min, held for 30 minutes, then heated to 950℃ and held for 120 minutes. After cooling to 200℃, it is thermally crushed for 6 minutes to make the particle size less than 0.30mm.

[0065] Step 5: Select hot-quenched steel slag particles with a particle size in the range of 0.3mm-0.8mm, grind them with a three-head grinder, and sieve them to obtain steel slag powder with a particle size of less than 0.10mm;

[0066] Step 6: Mix 24% heat-treated phosphogypsum, 12% heat-treated aluminum ash, 24% ground steel slag powder, and 40% 42.5 silicate cement evenly to obtain a composite cementitious material of heat-treated aluminum ash, heat-treated phosphogypsum, finely ground steel slag powder, and silicate cement.

[0067] Step 7: Stabilize the E2 aggregate mixture with the heat-treated aluminum ash, heat-treated phosphogypsum, finely ground steel slag powder, and silicate cement composite water-stabilized cementitious material prepared in Step 6. Control the water content at 8.5%; the aggregate soaking time is 16 hours; the curing conditions are 27℃ and 95.5% humidity. Other steps refer to the standard specification of "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering" JTG E51-2009.

[0068] Step 8: Test the unconfined compressive strength (UCS) and splitting tensile strength (SCS) of specimen B after 7, 14, and 28 days of curing, following the strength analysis procedure in the "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering" JTG E51-2009. The test results are shown in Table 1.

[0069] Step Nine: The nitrogen (N) content of the hardened specimen B (cured for 28 days), untreated phosphogypsum, and untreated aluminum ash was analyzed by energy dispersive spectroscopy (EDS). Then, leaching was performed according to the "Leaching Toxicity Method for Solid Waste - Horizontal Oscillation Method" (HJ 557-2010). Finally, the soluble phosphorus (P) leaching concentration was determined by ultraviolet-visible spectrophotometry, and the soluble phosphorus (F) leaching concentration was tested using the fluoride ion selective electrode method. The test results are shown in Table 2.

[0070] Example 6: Analysis of the effect of heat-treated aluminum ash-heat-treated phosphogypsum-finely ground steel slag powder-silicate cement stabilized steel slag-crushed stone gradation formula 2 on strength. The implementation steps are as follows:

[0071] Step 1: Take the hot slag and crush it using a jaw crusher. Separate the slag particles with diameters in the following ranges: 26.5mm-20.0mm, 20.0mm-15.0mm, 15.0mm-10.0mm, 10.0mm-4.75mm, 4.75mm-2.36mm, 2.36mm-0.8mm, 0.8mm-0.3mm, and 0.1mm-0.3mm.

[0072] Step 2: Weigh steel slag and natural crushed stone of different particle size ranges from Step 1 according to the E2 mixed aggregate formula in Table 1 to form mixed aggregate;

[0073] Step 3: Add 1.5% lime to the phosphogypsum, mix well for 2.5 minutes, heat at 160℃ under atmospheric pressure of 0.1MPa for 90 minutes, and then thermally crush for 2.5 minutes to reduce the particle size to less than 0.30mm.

[0074] Step 4: In a muffle furnace, the aluminum ash is heated to 780℃ at a temperature gradient of 10℃ / min, held for 30 minutes, then heated to 900℃ and held for 90 minutes. After cooling to 180℃, it is thermally crushed for 5 minutes to reduce the particle size to less than 0.30mm.

[0075] Step 5: Select hot-quenched steel slag particles with a particle size in the range of 0.3mm-0.8mm, grind them with a three-head grinder, and sieve them to obtain steel slag powder with a particle size of less than 0.10mm;

[0076] Step 6: Mix 16% heat-treated phosphogypsum, 8% heat-treated aluminum ash, 16% ground steel slag powder, and 60% 42.5 silicate cement evenly to obtain a composite cementitious material of heat-treated aluminum ash, heat-treated phosphogypsum, finely ground steel slag powder, and silicate cement.

[0077] Step 7: Stabilize the E2 aggregate mixture with the heat-treated aluminum ash, heat-treated phosphogypsum, finely ground steel slag powder, and silicate cement composite water-stabilized cementitious material prepared in Step 6. Control the water content at 8%; the aggregate soaking time is 14 hours; the curing conditions are 25℃ and 95% humidity. Other steps refer to the standard specification of "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering" JTG E51-2009.

[0078] Step 8: Test the unconfined compressive strength (UCS) and splitting tensile strength (SCS) of specimen C after 7, 14, and 28 days of curing. The procedure follows the strength analysis procedure in JTG E51-2009, "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering". The test results are shown in Table 1.

[0079] Step Nine: The nitrogen (N) content of the hardened specimen C (cured for 28 days), untreated phosphogypsum, and untreated aluminum ash was analyzed by energy dispersive spectroscopy (EDS). Then, leaching was performed according to the "Leaching Toxicity Method for Solid Waste - Horizontal Oscillation Method" (HJ 557-2010). Finally, the soluble phosphorus (P) leaching concentration was determined by ultraviolet-visible spectrophotometry, and the soluble phosphorus (F) leaching concentration was tested using the fluoride ion selective electrode method. The test results are shown in Table 2.

[0080] Analyze the microstructure of specimen A, which has been cured for 28 days, such as... Figure 1 As shown, the microstructure of the hardened specimen E2 after 28 days of curing was analyzed. Figure 2 As shown, combined with Figure 1 and 2It can be seen that the composite heat-treated aluminum ash-heat-treated phosphogypsum-finely ground steel slag powder-silicate cement composite water-stabilized cementitious material can enhance the strength of the water-stabilized layer by generating more fibrous morphology hydrated calcium aluminate (CAH) crystals and long columnar ettringite (AFt), so that its (specimen A) water-stabilized layer has higher mechanical properties than the all-silicate cement group specimen (E2).

[0081] Although the technical solutions of the present invention have been described and enumerated in detail, it should be understood that modifications to the above embodiments or the adoption of equivalent alternatives are obvious to those skilled in the art. Such modifications or improvements made without departing from the spirit of the present invention are all within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a roadbed water-stabilized layer using solid waste phosphogypsum, aluminum ash, and steel slag, characterized in that, It is prepared from solid waste-based cementitious materials and aggregates; The solid waste-based cementitious material, by mass percentage, consists of 16%-24% heat-treated phosphogypsum, 8%-12% heat-treated aluminum ash, 16%-24% steel slag powder, and 40%-60% silicate cement. The heat treatment method for the phosphogypsum is as follows: lime is added to the phosphogypsum, mixed evenly, heated under vacuum conditions, and finally thermally crushed. The heat treatment method for the aluminum ash is as follows: heating gradient 8-12℃ / min, heating to 750-800℃, holding for 30 minutes, then heating to 850-950℃, holding for 60-120 minutes, cooling to 150-200℃ and then hot crushing. The method for preparing the steel slag powder is as follows: hot-quenched steel slag particles with a particle size in the range of 0.3mm-0.8mm are ground with a three-head grinder and sieved to make the particle size less than 0.10mm; The aggregate is a mixture of hot-quenched steel slag and crushed stone, and consists of the following particle size components: hot-quenched steel slag and crushed stone mixture with a particle size of 26.5mm-20.0mm, hot-quenched steel slag and crushed stone mixture with a particle size of 20.0mm-15.0mm, hot-quenched steel slag and crushed stone mixture with a particle size of 15.0mm-10.0mm, hot-quenched steel slag and crushed stone mixture with a particle size of 10.0mm-4.75mm, hot-quenched steel slag with a particle size of 4.75mm-2.36mm, hot-quenched steel slag with a particle size of 2.36mm-0.8mm, hot-quenched steel slag with a particle size of 0.8mm-0.3mm, and hot-quenched steel slag with a particle size of 0.10mm-0.3mm.

2. The method for preparing a roadbed water-stabilized layer from solid waste phosphogypsum, aluminum ash, and steel slag according to claim 1, characterized in that, The process parameters for stabilizing steel slag-crushed stone aggregate using solid waste-based cementitious materials are as follows: water content is controlled at 7.5%-8.5%; aggregate soaking time is 12-16 hours; curing conditions are temperature 23℃-27℃ and relative humidity 94.5%-95.5%.

3. The method for preparing a roadbed water-stabilized layer from solid waste phosphogypsum, aluminum ash, and steel slag according to claim 1, characterized in that, The specific parameters for the heat treatment of the phosphogypsum are as follows: the amount of lime added is 1-2% of the weight of the phosphogypsum, the mixing time is 2-3 minutes, the atmospheric pressure is controlled at 0.08 MPa, the heating temperature is controlled at 150℃-170℃, the heating time is 60-120 minutes, the hot crushing time is 2-3 minutes, and the particle size of the phosphogypsum after hot crushing is less than 0.30 mm.

4. The method for preparing a roadbed water-stabilized layer using solid waste phosphogypsum, aluminum ash, and steel slag according to claim 1, characterized in that, The thermal crushing time of the aluminum ash is 4-6 minutes, and the particle size of the aluminum ash after thermal crushing is less than 0.30 mm.

5. The method for preparing a roadbed water-stabilized layer from solid waste phosphogypsum, aluminum ash, and steel slag according to claim 1, characterized in that, The proportions of each particle size of the aggregate, by weight percentage, are as follows: The proportions of hot-quenched steel slag and crushed stone in the particle size range of 26.5mm-20.0mm are both 2.5%-3.5%; The proportions of hot-quenched steel slag and crushed stone in the particle size range of 20.0mm-15.0mm are both 7.0%-8.0%; The proportions of hot-quenched steel slag and crushed stone in the particle size range of 15.0mm-10.0mm are both 5.5%-6.5%; The proportions of hot-quenched steel slag and crushed stone in the particle size range of 10.0mm-4.75mm are both 8.5%-11.5%; The proportion of hot-quenched steel slag with a particle size range of 4.75mm-2.36mm is 16.5%-17.5%; The proportion of hot-quenched steel slag with a particle size ranging from 2.36 mm to 0.8 mm is 16.5%-17.5%; The proportion of hot-quenched steel slag with a particle size of 0.8mm-0.3mm is 4.5%-5.5%; The proportion of hot-quenched steel slag with a particle size of 0.10mm-0.3mm is 9.5%-10.5%.

Citation Information

Patent Citations

  • A system and method for improving the chemical activity of steel slag

    CN110655341B

  • Biochemical preparation method of steel slag powder, cement mixed material and concrete admixture

    CN113493316A

  • Method for producing high-quality building gypsum through in-situ deep purification of phosphogypsum

    CN115180853A

  • Secondary aluminum ash for concrete and treatment method thereof

    CN115180857A

  • NRC Acid-Resistant and Freeze-Thaw Resistant Composite Leak-Proof Material Based on Phosphogypsum and Its Preparation Method

    CN115340347B